Pemetaan Data Usaha Mikro Kecil dan Menengah dan Pendaftaran Nomor Induk Berusaha di Desa Tremes, Kecamatan Sidoharjo, Kabupaten Wonogiri, Jawa Tengah - Dany Farel Ega Arsanto; Aulia Arifa; Aditya Bagas Calosa; Bagas Yulianto; Devi Novitasari Putri Wibowo; Dwi Meisari; Endika Sofya Pramesti; Gaizka Mahdafikia; Qonita Luthfiyah; Ranita Restu Nur Azizah; Mujiyo Mujiyo (AgriHealth: Journal of Agri-food, Nutrition and Public Health, 2021)
Business Registration Number (BRN) is the identity of business actors in the context of carrying out business activities according to their business fields. NIB is important for business actors to take care of matters regarding business licensing. One of the purposes of NIB ownership is to provide convenience in obtaining capital assistance and business development. Data mapping activities for Micro, Small and Medium Enterprises (MSMEs) and registration of Business Identification Numbers (NIB) were carried out in Tremes Village, District, Sidoharjo District, Wonogiri Regency. The low NIB ownership of business actors in Tremes Village, while the high number of MSMEs encourages this activity. Activities are carried out by 1) socialization; 2) data input training using https://oss.go.id in direct partnership with the Investment and One Stop Service Office; 3) distribution and collection of forms; 4) data input and issuance of Business Registration Number (BRN) and; 5) submission of the Business Registration Number (BRN) to the public. This activity aims to map data and help manage micro, small and medium enterprises. Mapping of MSMEs data in Tremes Village makes it easier for the village government to get MSMEs data and facilitates the process of distributing MSMEs assistance on target. The total number of MSMEs that have been recorded in Tremes Village is 459 businesses. There were 454 BRNs (99.34%) of the 457 MSMEs that registered. Follow-up from the issuance of the BRN in Tremes Village was the submission of Productive Micro Business Assistance to the Office of Cooperatives, Small Medium Enterprises, Industry and Trade, Wonogiri Regency.